2022
DOI: 10.1002/adom.202200930
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐Tuning Single‐Source White‐Light Emission from All‐Inorganic Corrugated 2D Antimony‐Halide Perovskite

Abstract: Corrugated 2D antimony‐halide perovskites such as Cs3Sb2Cl9 (CSC) are promising candidates for single‐source white‐light emission due to their ultra‐broadband spectra. However, CSC has a serious luminescence quenching phenomenon due to inadequate confinement of excitons. By the homovalent substitution of trivalent antimony cation Sb3+ by a small amount of trivalent rare earth (RE) cations RE3+, the photoluminescence intensities from high‐quality Cs3(Sb1−xREx)2Cl9 (CSRC) (RE = Ce, Sm, Nd, Y, Er, etc.) films at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 70 publications
1
10
0
1
Order By: Relevance
“…By fitting the PL spectra at 10 K, it is found that both of them consist of two Gaussian peaks positioned at 540 and 600 nm, respectively, as shown in Figure S3a,b. Similar to our previous work, the emission at 540 nm also exhibits a slight blueshift with increasing operating temperature (Figure S4), 40 which is consistent with the luminescence properties of the STE emission. 43 Another Gaussian peak at 600 nm is more pronounced at lower temperatures, following the characterization of the defect emission, 44 the mechanism of which will be revealed in the theoretical part below.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…By fitting the PL spectra at 10 K, it is found that both of them consist of two Gaussian peaks positioned at 540 and 600 nm, respectively, as shown in Figure S3a,b. Similar to our previous work, the emission at 540 nm also exhibits a slight blueshift with increasing operating temperature (Figure S4), 40 which is consistent with the luminescence properties of the STE emission. 43 Another Gaussian peak at 600 nm is more pronounced at lower temperatures, following the characterization of the defect emission, 44 the mechanism of which will be revealed in the theoretical part below.…”
supporting
confidence: 91%
“…Cs 3 Sb 2 Cl 9 Films Fabrication: Materials, Cs 3 Sb 2 Cl 9 powders fabrication, and characterizations refer to our published work. 40 Here, we focus on the Cs 3 Sb 2 Cl 9 films fabrication and theoretical calculations method. Figure S1 shows the schematic representation of the improved solution-processing spin-coating method to prepare thin films of layered Cs 3 Sb 2 Cl 9 .…”
Section: Csmentioning
confidence: 99%
See 3 more Smart Citations